Abylaikhan role in defending the national state and its political and legal views (Journal of actual problems of jurisprudence, 2018)
Article is devoted to the political and legal views Abylaikhan who was able during the great tribulation, during the war for independence from Jungaria unite the people to defend the state independence. Abylai Khan putting its purpose to defend the independence was the last ruler who was able to combine all three Kazakh Juz. Abylai Khan and as a diplomat and as a legislator has dedicated his work the unity of the nation and its strengthening.Key words: monarchism, the concentration of power, freedom, the will, independence, unity.